Recurrence Patterns and Long-term Results After Induction Chemotherapy, Chemoradiotherapy, and Curative Surgery in Patients With Locally Advanced Esophageal Cancer. Issue 1 (January 2019) - Steffen, Thomas; Dietrich, Daniel; Schnider, Annelies; Kettelhack, Christoph; Huber, Olivier; Marti, Walter R.; Furrer, Markus; Gloor, Beat; Schiesser, Marc; Thierstein, Sandra; Brauchli, Peter; Ruhstaller, Thomas
Abstract : Objective: The long-term follow up data of 2 prospective phase II trials is reported (NCT00072033, NCT00445861), which investigated neoadjuvant chemoradiation followed by surgery in patients with esophageal carcinoma. Postoperative complications as well as prognostic factors and patterns of relapse during long-term observation are shown. Summary of Background Data: Long-term follow-up is often missing in the complex setting of multimodal treatments of esophageal carcinoma; this leads to rather undifferentiated follow-up guidelines for this tumor entity. Methods: In the first trial, patients received induction chemotherapy followed by chemoradiation and surgery. In the second trial, cetuximab was added to the same neoadjuvant treatment concomitant with induction chemotherapy and chemoradiation. Results: Eighty-two patients underwent surgery; the median follow-up time was 6.8 and 6.4 years, respectively. Fifty-five percent were diagnosed with adenocarcinoma, 80% clinically node-positive, 68% received transthoracic esophagectomy, and 32% transhiatal or transmediastinal resection. Five patients died postoperatively in-hospital due to complications (6%). The median overall survival was 4.3 years, and the median event-free survival was 2.7 years. Patients with adenocarcinoma rarely relapsed after a 3-year event-free survival. Whereas patients with residual tumor cells after neoadjuvant therapy primarily experienced relapse within the first 2 postoperative years, this in contrast to several patients with complete remission who also experienced late relapses 4 years after surgery. Conclusion: After curative surgery in a multimodal setting, the histological type and the response to neoadjuvant therapy predicted the time frame of relapse; this knowledge may influence further follow-up guidelines for esophageal carcinoma.